Extraction and characterization of tannin from Mangifera Pajang (Bambangan) peels using different extraction methods - Azreen Ibrahim; S. Murni; M. Norfazrina; A. Y. Zahrim (IOP Publishing Ltd., 2025)
Mangifera pajang is a seasonal tropical fruit tree native to Southeast Asia, known for its significant phytochemical compounds and antioxidant properties. Due to its tannin content, it can be utilized as a natural coagulant for water and wastewater treatment, offering an alternative to chemical coagulants, which are often unsustainable and have various disadvantages. This study aims to extract tannin from the peel of Mangifera pajang by exploring three extraction methods: solid-liquid extraction (SLE), soxhlet extraction (SE), and ultrasonicassisted extraction (UAE). The total tannin content (TTC), radical scavenging activity (RSA), and percentage yield were measured to determine the most effective extraction technique. The findings revealed that the SLE method yielded the highest tannin content, with an approximate TTC of 10.14%. Additionally, the SLE method showed antioxidant activity of 85%-86% and a percentage yield of 94.85%, outperforming the SE and UAE techniques.